Implementasi Psikologi Manajemen dalam Pengelolaan Sekolah yang Efektif - Septa Tria Dinar; Lathifatur Robbaniyyah; Julian Liew; Siti Zainiyah; Mu’alimin Mu’alimin (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
This study aims to examine the implementation of management psychology in effective school management, highlighting the importance of psychological approaches in supporting teacher performance, educational staff welfare, and student engagement. Using a literature study method, data were collected from various academic sources in the last five years and analyzed descriptively-qualitatively to identify concepts, strategies, and the impact of management psychology in educational environments. The results of the study indicate that the application of management psychology principles such as democratic leadership, empathetic communication, and motivational reinforcement can create a conducive work climate, improve teacher performance, and support the effectiveness of overall school management. By understanding the psychological dynamics of individuals in schools, educational institutions can be more adaptive in facing challenges and creating a productive and holistic learning environment.